Self-phase modulation in a thin fused silica plate upon interaction with a converging beam of down-chirped femtosecond radiation. (31st May 2015) - Grudtsyn, Ya V; Zubarev, I G; Koribut, A V; Kuchik, I E; Mamaev, S B; Mikheev, L D; Semjonov, S L; Stepanov, S G; Trofimov, V A; Yalovoi, V I
Abstract The mechanism of spectral broadening and self-compression of down-chirped femtosecond pulses in the visible range (473 nm) upon nonlinear interaction of a converging Gaussian beam with a 1-mm-thick fused silica plate is experimentally and theoretically investigated. It is found experimentally that when the intensity increases and plasma is formed in the sample, the regime of femtosecond pulse splitting is transformed into the single-pulse generation regime during nonlinear interaction. As a result of selfcompression, the duration of the initial transform-limited pulse is reduced by a factor of 3. Based on the numerical solution of the generalised nonlinear Schrödinger equation, with the plasma formation disregarded, it is shown that the profile, spectrum and temporal phase of the pulse transmitted through the sample acquire a stationary shape behind the focal plane of the focusing mirror. The calculation results are in good agreement with experimental data. The possibility of parametric amplification of the pulse spectral components under given experimental conditions is discussed.